Quality of water bodies in the extreme south of Bahia, Brazil - Matias, Maria Iraildes de Almeida Silva; Santos, João Victor da Silva; Freitas, Rômulo Magno Oliveira; Matias, Larissa Carolina Silva (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2018)
Water is a natural resource indispensable to life, has enormous economic, environmental and social value, and it is fundamental to the survival of humans and ecosystems on our planet. Surface water must meet standards of quality and drinkability, and its physical, chemical and biological characteristics should meet the standards recommended by the World Health Organization. The present study aimed to evaluate the physical-chemical and biological properties of surface water of three water bodies in the Municipality of Teixeira de Freitas, Bahia. The following parameters were evaluated: BOD (Biochemical Oxygen Demand), Total Phosphorus, Total Nitrogen, Dissolved Oxygen, pH, Total Solids, Turbidity and Thermotolerant Coliforms. The evaluation showed that all of the three water bodies are contaminated and in disagreement with the limits established in CONAMA Resolution No. 357/05 for Class 2 freshwater. In addition, one of the three water bodies showed signs of eutrophication.